METAFORA DALAM LIRIK LAGU KOKORO NO TOMO KARYA ITSUWA MAYUMI - Akhmad Saifudin (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
This article discusses the meaning of the metaphor contained in the Japanese song’s lyrics. With the use of metaphor analysis